Model Fisik Sub Surface Flow Constructed Wetland Untuk Pengolahan Air Limbah Musala Al-Jazari Fakultas Teknik Universitas Riau - Hidayat, Taufiq; Darmayanti, Lita; Sujatmoko, Bambang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Musala Al-Jazari is located in the Faculty of Engineering, University of Riau. Activity in musala every day produces a wastewater effluent. Wastewater directly discharged and allowed to seep in flooded soil without first processing that can affect groundwater quality. One of the appropriate technology is simple, inexpensive and easy in operation and maintenance system to reduce pollutants in wastewater was constructed wetland. The purpose of this study is to plan physical model of Sub Surface Flow Constructed Wetland (SSF-Wetland) field scale, determine the effectiveness of SSF-wetland in reducing water waste and calculate budget construction costs SSF-Wetland. Research using medium black soil and water jasmine plants (Alisma plantago). Water quality parameters tested were pH, Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS). The results of the study resulted in the highest efficiency value of 78.07% reduction in COD, TSS of 78.72% and an increase in the pH value of 27.59%. From planning SSF-Wetland obtained the total planned budget of Rp. 6,574,527.16. Overall the results showed that the constructed wetland besides being able to improve the quality of waste water can also beautify the area musala. Â Keywords: wastewater, constructed wetland, alisma plantago